Measuring and interpreting trait‐based selection versus meta‐community effects during local community assembly. (8th April 2013) - Shipley, Bill; Fridley, Jason
Abstract Questions (1) How can one quantify the relative importance of meta‐community processes related to immigration, local trait‐based habitat filtering, and demographic stochasticity using the Community Assembly by Trait Selection (CATS) model in a general context? (2) How can this generalization be used to detect different strengths and directions in trait selection at the meta‐community and local community levels? Methods I describe a decomposition of the deviance between observed and predicted relative abundances based on a maximum entropy model including a meta‐community prior (CATS) and generalize a previous decomposition of relative abundance using this model; corrections to avoid negative explained proportions of deviance are presented. Simulations of community assembly are used to explore its properties and elucidate its interpretation. In particular, this method quantifies the proportion of the total deviance between observed and predicted relative abundances attributed to: (1) pure trait‐based local selection, (2) dispersal mass effect from the meta‐community, (3) joint contributions of (1) and (2) that cannot be separated; and (4) residual deviance due to demographic stochasticity. Results and Conclusions The previous decomposition, while giving correct values in that particular data set, requires modification in order to avoid nonsensical negative values. When the modifications described in this paper are made, the decomposition provides correct values. Furthermore, positive or negative values of the joint composition inform us of the importance and direction of correlations between local trait‐based selection and processes occurring in the larger meta‐community.